Substantiation of rational characteristics of mechatronic control systems of position Of wheel pairs (Transport systems and technologies, 2020)
The article analyzes the schematic diagrams of rail vehicles with radial installation of wheelsets. Radial installation of wheelsets in curved sections of the track allows for optimal interaction of wheels and rails. This interaction is characterized by minimal lateral forces in the contact of the wheels and the rails and a decrease in wear of their contacting surfaces. Requirements are formulated for the characteristics of hardware and software that will ensure the technical implementation of mechatronic control systems for the position of wheel pairs of rail vehicles in the rail track in the horizontal plane. The devices included in the mechatronic automatic control system must represent a single closed system in which the parameters of various electrical, mechanical and hydraulic processes are inextricably linked. Due to the high requirements for reliability and time constraints to the formation and transmission of the control signal to the actuators, the operation of such a system for rail vehicles should be carried out in real time. A schematic diagram of a mechatronic positioning system for wheel sets is proposed, which allows them to be optimally mounted on a railses under various conditions of vehicle movement. On the example of movement a three-axle bogie of a 2TE116 diesel locomotive in the curve, comparative calculations are made. The calculation results showed the possibility of a significant reduction in the guiding forces and minimizing the attac angles of the wheelsets of the modernized bogy in comparison with the standard design bogy.
Keywords: rail vehicle, wheelset, radial installation, control, actuator, mechatronic system.